Is Estimated Glomerular Filtration Rate (eGFR) a Better Predictor than Creatinine Cutoff to Detect Chronic Kidney Disease (CKD)? (Ibrahim Medical College Journal, 2016)
Chronic kidney disease (CKD) with diabetes mellitus is one of the most common and major public health problems globally. In Bangladesh, several studies indicate an increasing prevalence of diabetes though very few studies are available on CKD. For CKD, diagnostic method, criteria or cutoffs still remained undecided. This study aimed to determine the prevalence of CKD among the hospitalized patients and to compare the diagnostic approach practiced in the hospital. Methods: All patients admitted to the Department of Nephrology at BIRDEM from May 1 to July 31, 2012 were selected for investigation. An almost equal number of patients were also selected from other units of Medicine. The information included were age, sex, social class, blood pressure, height, weight, blood glucose, creatinine, triglycerides, total cholesterol, high-density lipoproteins and electrolytes. The CKDcreat was diagnosed based on creatinine (>1.2mg/dl) and the CKDgfr based on estimated GFR (1.2 mg/dl) groups. Similar comparisons were also made between CKDgfr and non-CKDgfr (>60 vs. ? 60 ml/min/1.732) groups. Results: A total of 4172 patients got admitted in the study period of 90 days; and 442 patients (m / f = 256 / 186) were investigated. Of the total (n=4172), 241 (5.8%) had CKDcreat and 272 (6.5%) had CKDgfr. Of the investigated 442 patients, 241 (54.5%) had CKDcreat and 272 (61.5%) had CKDgfr. The differences of characteristics between CKDcreat and non-CKDcreat groups were almost similar to the differences between CKDgfr and non-CKDgfr groups. Higher age, higher social class and higher blood pressure showed significant (p